The Argentine vaccine during the “Spanish flu”, 1918-1919. Theoretical debates and development of a therapy on the periphery of science - Carbonetti, Adrián (2021)
In this article, we analyze the development and testing process for a vaccine against the “Spanish flu” in Argentina, the only country in Latin America that took part in the discussions about the etiological agent that caused the influenza of 1918-1919. We note that multiple theories emerged about this agent, which derived from the hypotheses employed in developed countries. These discussions influenced the development of a vaccine that was conceived on the peripheries of world science. We start from the hypothesis that, despite its peripheral position, state action in Argentina led to the development of the vaccine through the establishment of institutions for this purpose and the hiring of European scientists. We describe and analyze the medical debates concerning the causes of the disease, especially the deliberations at the Faculty of Medicine of the University of Buenos Aires. We then go on to describe the development of the vaccine at the Bacteriological Institute and its application during the two flu outbreaks in Argentina. Resources used include government documents, medical publications, and press coverage.